Prevention of Violence and Sexual Abuse in Early Childhood Through Implementation of Sex Education in the Perspective of the Sunnah - Camelia, Lely; Nirmala, Ine (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2016)
This article discusses the conceptual studies on the implementation of early childhood sex education according to Islamic perspective. The number of cases of violence and sexual abuse against children has recently made various parties, no exception for parents, that must be alert to the threat. The big point of that is in 2015 when Indonesian Child Protection Commission said that cases of violence and abuse against children is a latent danger for the children of Indonesia. Several attempts have been made, some like starting to give a sex education early for parents and children, limiting the viewing access to pornography, limiting the contents of pornography on the internet and games, and stopping the attempts of the perpetrators in violence and sexual abuse against children by give them the weightest punishments. Rasullullah SAW as good role model has provided some guidance for us on how to educate children in detail, not only about early sex education, but also how to educate them since they are in the loins of their father. With reference to the sunnah that has showed by our Prophet to us, we as teachers and parents can apply it in everyday life, that will have a positive impact on children and the environment in the prevention of violence and sexual abuse against children.  Keywords: sex education, children, islamic perspective, Prophetâs sunnah perspective